Ex-situ conservation strategies in South African indigenous goat genetic resources - Chokoe, Tlou Caswell (My University, 2025)
The study was undertaken to investigate the genetic adaptation in South African communal indigenous goat populations using the socio-economic status, phenotypic traits, Illumina SNP50K data, and conservation strategies approaches. Proper conservation strategies become important for endangered breeds/populations and those that are not properly utilized. Ex Situ conservation objectives include avoiding extinction, maintaining genetic diversity and incorporating the cultural and socio-economic merit of breeds/populations. The first objective of the study was to characterize the socio-economic factors influencing indigenous goat value and production constraints in selected rural areas of South Africa. Individual interviews were conducted in 241 households using semi-structured questionnaires from four randomly selected provinces of South Africa; namely Free State (FS), Gauteng (GP), Limpopo (LP) and North West (NW) respectively. Data were analysed using Statistical Package for Social Science (SPSS 26.1 for Windows) for multifactorial analysis of variance and covariance. The major constraints to indigenous goat production were unavailability of feed (85 %) followed by low indigenous goat sales (72 %) and their value by the indigenous farmer (60 % of the households). Odds ratios for selling goats were high for the following predictors: age of the head of household, farm size, production system, mating system, external parasite control, belong to union and source of breeding bucks. To effectively address production constraints faced by indigenous goat farmers, it is therefore, fundamental to consider their socioeconomic profiles. The second objective of the study was to determine the phenotypic diversity of South African indigenous goat population in selected rural areas. Appearance of indigenous goat phenotypes and their typical features were observed from 297 individual goats. There was a significant (P<0.05) difference in all phenotypic measurements, with higher (P<0.05) values for body length (48.23 cm), body weight (26.86 kg) and wither height (64.61cm) observed in indigenous goats of Dr. Ruth Segomotsi Mompati (DRSM) region. The indigenous goats of the Thabo Mofutsanyana region had the highest (P<0.05) value for rump length (17.52 cm), however, have the shortest tail length (7.17 cm) compared to those at other regions. Results from the study show considerable xviii phenotypic heterogeneity in qualitative traits of the indigenous goat population and their distributions in different regions. The third objective was to determine genetic diversity of South African Communal indigenous goat population using genome-wide SNP data. Communal indigenous goat populations were genotyped using the Illumina Goats SNP50 BeadChip. Analysis of molecular variance revealed variations of 3.39% (P< 0.0001) and 90.64% among and within populations, respectively. The first two PCAs, and revealed a unique Limpopo population separated from GP, FS and NW Communal indigenous goat populations with high levels of admixture with commercial goat populations. Population differentiation tests (PCAdapt) revealed PC2 as optimal and 5 outlier SNPs were detected on chromosomes 10, 15, 20 and 21. The study revealed that the SNPs identified by the first two principal components show high FST values in LP Communal goat population and allowed to identify candidate genes which can be used in the development of breed selection programs to improve this unique LP population and other Communal goat population of FS, GP and NW and find genetic factors contributing to the adaptation to harsh environments. Lastly, conservation status and historical relatedness of South African indigenous goat populations using genome-wide SNP marker was determined as part of the fourth objective of the study. Across populations, the current Ne of Gauteng was the lowest at 371 animals, while the historical Ne across populations suggests that the ancestor Ne has decreased by 53.86%, 44.58%, 42.16% and 41.16% in Free State (FS), North West (NW), Limpopo (LP) and Gauteng (GP), respectively, over the last 971 generations. Genomic inbreeding levels related to ancient kinship (FROH >5Mb) was highest in FS (0.08±0.09) and lowest for Eastern Cape (EC) (0.02±0.02). The genomes of KZN and LP shared an origin but have substantial admixture from the EC and NW populations. The use of Illumina goat SNP50K BeadChip shows that there was a migration route of communal indigenous goat populations from the northern part (LP) of South Africa to the eastern areas of the KZN, that confirmed their historical relatedness and which coincide with the migration periods of the Bantu nation
Thesis (Ph. D. (Animal Production)) -- University of Limpopo, 2025
Keywords: Households; Production system; Socioeconomic; Body length; Characterisation; Coat colour; Goat farming; Goats -- Breeding; Animals -- Colour